A Literature Review of Feedback Timing on Reading Comprehension in China and Abroad - Qia, Di; Rajab, Azizah; Balqis Haladin, Nur’ain; Wang, Wenjing; Fu, Xiaoxiao (International Journal of Psychosocial Rehabilitation, 2020)
Since the 21st century, Chinese scholars have been engaged in research on the teaching strategy and effectiveness of teacher feedback in the field of oral English and writing. However, in general, there is very little relevant research related to teacher feedback on reading comprehension in China. In this study, it compares studies of feedback on reading comprehension in China and abroad, especially paying attention to the feedback timing on reading comprehension. This study shows distributing research with detailed resources. Some possible reasons are put forward in this research field; meantime, some implications in the research of feedback timing on reading comprehension are given in the conclusion.